ANALISIS JENIS TANAH UNTUK DESAIN FONDASI PADA GEDUNG MABES POLRI DI IBU KOTA NUSANTARA (IKN) - Raafidiani, Reni; Ravelo, Algia; Febriansya, Aditia (Jurnal TEDC; Vol 20 No 1 (2026): JURNAL TEDCDO - 10.70428/tedc.v20i1.1441, 2026)
The relocation of the national capital to Penajam Paser Utara requires infrastructure planning that is adaptive to local geotechnical conditions, including the construction of the National Police Headquarters building. This study evaluates soil characteristics through laboratory testing at three borehole points (BH-01, BH-02, BH-03) to determine the physical and mechanical parameters of the soil. Based on the test results at the CND Geoteknika Laboratory, which included grain size analysis, Atterberg limits, consolidation, triaxial and direct shear tests, it was found that the soil at the site was dominated by clay fractions (81–89%) and classified as CH (fat clay) soil with high plasticity. This characteristic is marked by a liquid limit of 61–67% and a plasticity index of 40–49%, which indicates significant swelling and shrinkage potential as well as easily compacted properties with a compression index of 0.20–0.31. Shear strength parameters show a cohesion value of 31–62 kN/m² with varying angles of friction. The implication is that the condition of this expansive clay soil poses a risk of settlement and long-term structural instability. Therefore, this study recommends the use of deep foundations or soil improvement methods as geotechnical mitigation strategies to ensure the safety and structural performance of the National Police Headquarters Building in the future.